Uji Ekstrak n-Hexana Rumput Kebar (Biophytum petersianum Klotzsch) pada Tikus Wistar Hiperkolesterolemia - Priyo Sambodo; Purwaningsih Purwaningsih; Alnita Baaka; Trini Susmiati; Claude Mona Airin (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
This study was aimed to determine the secure level of the n-hexane extract of kebar grass on hypercholesterolemia rats based the acute oral toxicity test. Based the literature, no report on the toxic dosage before, initial dose was started at 300 mg/kg body weight (BW) and to be increased 2000 to 5000 mg/kg BW. Toxicity data were set for 24 hours and continued until 14 days after treatment for several parameters, i.e : toxicity symptoms, death of animals, changes in body weight and the manifestation of toxicity effects. At the end of the test, the rats were sacrificed and organs were taken for abnormalities (macroscopy). The results of this study showed that the administration of the n-hexane extract of grass kebar at all doses did not show the toxicity symptoms, mortality and body weight change. The absolute and relative weights and gross pathology observation of the internal organ were normal. Conclusions: the n-hexane extract of grass kebar is safe and the LD was determined on category 5, 50 unclassified or minimum practically non toxic